Dynamic Spatial Confluence of Residential Construction Initiations Autocorrelation in Tel Aviv-Yafo 1976-2003 - Idan Porat; Maxim Shoshany; Amnon Frenkel (European Regional Science Association (ERSA), 2006)
The present study examines the spatial development of the residential build area in the city of Tel Aviv-Yafo, a metropolitan core city and a world city in evolution, over the course of 30 years. We employed spatial autocorrelation model in order to test the urban development of the city built-up area. The analysis presented in this paper is unique in a sense of using spatial autocorrelation model on residential Construction Initiations (CI) information that represent additional and renewal of built floor area (FA), its land use and location. The suggested spatial autocorrelation model used annual and accumulative CI as a database for urban growth analysis. We consider spatial autocorrelation (Moran I) as a statistic tool for urban growth analysis. The combination of long time series of CI (available since the middle seventies at a sub-quarters resolution) enable to test the data on annual and accumulative base, thus contribute to the examination of spatial urban processes. The results obtained from employing the various autocorrelation indices used in the study (Moran: Annual and Cumulative) show significantly high clustering level of the residential accumulative CI system in Tel Aviv-Yafo. Such result was partly expected due to the development of new residential areas in Northern Tel Aviv. However, there is another interesting component of this clustering which relates to the regeneration in the older neighborhoods. Assessment of the differences between the yearly and accumulative autocorrelations allows new insight into the urban CI dynamics, whereby the annual data show a tendency toward a more random spatial organization in parallel to the accumulation into clusters. Generalizing this new phenomenon is expected to contribute to the understanding of the evolution of urban regions undergoing both expansion and internal renewal.
Keywords: 330